The Analysis of Inflammation-Related Proteins in a Cargo of Exosomes Derived from the Serum of Uveal Melanoma Patients Reveals Potential Biomarkers of Disease Progression - Wróblewska, Joanna Patrycja; Lach, Michał Stefan; Kulcenty, Katarzyna; Galus, Łukasz; Suchorska, Wiktoria Maria; Rösel, Daniel; Brábek, Jan; Marszałek, Andrzej (Cancers, 2021)
BACKGROUND: Uveal melanoma (UM) is the most common intraocular tumour in adults with a poor prognosis and extremely high mortality rate due to the development of metastatic disease. However, despite relatively good knowledge about the histological and genetic risk factors for metastasis development, there is no specific biomarker that would allow early detection of UM progression. Recently, exosomes and their molecular cargo have been widely studied in the search for potential biomarkers in several cancers. The purpose of this study was to analyze the inflammation-related protein cargo of exosomes derived from the serum of primary and metastatic UM patients and healthy donors. METHODS: The exosomes were isolated from the serum of primary and metastatic UM patients and healthy donors. Using multiplex immunoassay technology, we analyzed the concentration of 37 inflammation-related proteins in obtained exosomes. RESULTS: The analysis of protein cargo showed several molecules related to inflammation, such as interferon-gamma, interleukin 2, 22 and 12(p40), Pentraxin-3, TNFSF13B and TNFSF8 which were significantly enriched in metastatic UM exosomes. We showed a significant correlation between the disease stage and the concentration of these inflammation-related proteins from exosomal cargo. CONCLUSIONS: Based on the obtained results, we propose the panel of exosomal proteins for early detection of uveal melanoma progression into metastatic disease.
Keywords: inflammation-related proteins; uveal melanoma; exosomes; biomarkers